Green city initiatives: Human-nature interaction - Bakar A.A.; Mustapa S.I.; Mohammad N. (Malaysian Institute Of Planners, 2023)
Interaction with Nature [IN] refers to the urge or preference to be close to the natural environment, attentiveness and knowledge of the natural environment, and health associated attributes in relation to surroundings. Issue: Since the vision of green city was introduced, Melaka has made great strides toward building a sustainable, green city. With the ongoing development towards reduction of carbon intensity 2020, IN of Melaka public needs to be evaluated to determine the human-nature connection with respect to the green initiative efforts. Purpose: This paper aims to compare the IN of Melaka residents to residents of other states in Malaysia. Approach: One-Way MANOVA was generated to determine the mean distribution of 10 IN items, across Malaysia States. Findings: There were significant differences within subjects of the 10 IN items between-subjects of Malaysia States. The Post-Hoc Test indicated majority of the means of IN items for Melaka were significantly higher than other states. However, in relation to other states, Melaka was slightly shy on (i) IN2, being able to recall experiences in the natural environment, and (ii) IN5, being able to notice scientific details of nature. 2021 Malaysian Institute Of Planners. All rights reserved.